Juridical Issues of Land Ownership Rights in Mixed Marriages in Indonesia - Alayna Lita Agzia Khalfani; Mira Novana Ardani (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
The increasing number of mixed marriages between Indonesian citizens and foreign nationals has created legal challenges regarding land ownership rights in Indonesia. These challenges arise from the inconsistency between the Basic Agrarian Law, which strictly applies the nationality principle, and the Marriage Law, which recognizes joint marital property. This study aims to analyze the legal regulation of land ownership in mixed marriages, identify the normative conflicts between agrarian and marriage law, and formulate strategies to strengthen legal certainty. This research employs a normative juridical method using statutory and conceptual approaches. Legal materials were collected through library research and analyzed qualitatively using a descriptive-analytical method. The findings reveal that the interaction between the nationality principle and the concept of joint marital property creates significant legal uncertainty for Indonesian citizens who marry foreign nationals, particularly in the absence of a marital agreement. Although Constitutional Court Decision Number 69/PUU-XIII/2015 permits postnuptial agreements and provides greater legal protection, it has not fully resolved the existing regulatory inconsistency. Therefore, harmonized agrarian and marriage laws, stronger institutional coordination, and greater public legal awareness are essential to ensure legal certainty and protect the land ownership rights of Indonesian citizens.